Regenerative and adjunctive surgical strategies in peri-implantitis: A mini-review - Halim, Susanna; Pratiwi, Tari Dwi; Christine, Christine; Farrent, Ellen Florencia; Meliala, Ivan Melka Sembiring (Jurnal Prima Medika Sains, 2025)
Peri-implantitis is a major biological complication that threatens the long-term success of dental implants. The progression from peri-implant mucositis to advanced bone loss often necessitates a shift from non-surgical to surgical treatment, although the most effective management protocols remain under debate. This mini-review aims to evaluate and compare clinical outcomes of three distinct approaches to peri-implantitis management: the diagnostic necessity of surgical access, conventional guided bone regeneration (GBR) combined with antibiotics, and adjunctive topical oxygen therapy. A narrative review was conducted, and three representative clinical case reports were purposively selected for detailed analysis. These cases illustrate different therapeutic strategies currently applied in clinical practice. The findings emphasize that surgical intervention is crucial for halting disease progression when non-surgical access proves inadequate. Conventional GBR supplemented with local antibiotics provided exceptional stability during a 17-year follow-up period. In contrast, the application of a topical oxygen gel (BlueM) yielded encouraging 5-year outcomes, demonstrating reduced inflammation and enhanced bone regeneration without the use of antibiotics. The success of all treatment modalities depended heavily on meticulous surface decontamination and thorough defect debridement. Surgical management of peri-implantitis should be tailored to the specific defect morphology. While GBR with antibiotics remains a well-established long-term reference, adjunctive oxygen therapy offers a promising non-antibiotic alternative for infection control. Further randomized controlled trials are warranted to establish standardized clinical protocols.